Правові засади взаємодії та координації діяльності правоохоронних органів на регіональному рівні - Русецький, А. А.; Rusetskyi, A. A. (Науковий вісник публічного та приватного права. - 2016. - Вип. 2, ч. 4. - С. 248-254, 2016)
У статті на основі аналізу наукових поглядів вчених та норм чинного законодавства України розглянуто правові засади взаємодії і координації діяльності правоохоронних органів на регіональному рівні та визначено місце серед них адміністративно-правового регулювання.

In the article, on the basis of the analysis of scientific opinions of scientists and norms of the current legislation of Ukraine, the legal principles of interaction and coordination of activity of law enforcement bodies at the regional level are considered and the place of administrative-legal regulation among them is determined. It is noted that the system of legal principles of interaction and coordination of law-enforcement bodies at the regional level is a fairly extensive system of legal acts. This aspect is directly related to the fact that in this area there is still no single normative document that would regulate all the points associated with the given problem. It was established that the legal principles of interaction and coordination of activity of law enforcement bodies at the regional level are the rules of legal acts of various legal force, the provisions of which to varying degrees regulate the specified categories. The position that the current CPC clearly defines all aspects of the criminal process, as well as the legal status and features of cooperation of law enforcement bodies within the framework of the latter is upheld. In the context of our study, the Criminal Procedural Code is interesting because its provisions reflect all aspects of the interaction of the relevant government departments. In addition, these provisions are also important for the organization of interaction and coordination of law enforcement activities at the regional level. It is substantiated that law enforcement agencies are in the vast majority of executive bodies, therefore, various aspects of their activities, in particular, the organization of interaction and coordination at the regional level, are regulated by the provisions of the Law of Ukraine “On Central Executive Bodies”. It is established that for today the basis of these categories is the provisions of a large number of normative legal acts. At the same time, in most cases, the latter regulate organizational issues, such as, the division of competences of law enforcement agencies, definition of their legal status, features of cooperation, etc. This aspect shows that the dominant role in the system of legal principles is given precisely to the norms of administrative acts on which the mechanism of administrative and legal regulation is based.

В статье на основе анализа научных взглядов ученых и норм действующего законодательства Украины рассмотрены правовые основы взаимодействия и координации деятельности правоохранительных органов на региональном уровне и определено место среди них административно-правового регулирования.
Keywords: адміністративно-правове регулювання; координація; взаємодія; правоохоронні органи; регіональний рівень; administrative and legal regulation; coordination; interaction; law enforcement bodies; regional level; административно-правовое регулирование; координация; взаимодействие; правоохранительные органы; региональный уровень